Vertical Differentiation in a Cournot Industry: The Porter Hypothesis and Beyond - Luca Lambertini; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We modify the vertically differentiated duopoly model by André et al. (2009) replacing Bertrand with Cournot behaviour to show that firms may spontaneously adopt a green technology even in the complete absence of any form of regulation.
Keywords: L13; L51; Q55; Q58; 330